Hydrogen embrittlement in high interstitial alloyed 18Cr10Mn austenitic stainless steels - Phaniraj, M. P.; Kim, Han-Jin; Suh, Jin-Yoo; Shim, Jae-Hyeok; Park, Seong-Jun; Lee, Tae-Ho (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
The effect of hydrogen on the tensile behavior of two 18Cr10Mn austenitic steels having the similar stacking fault energy but different nitrogen and carbon contents was investigated. The steels were thermally charged with hydrogen at 15 MPa and 300 degrees C. The hydrogen content was determined using thermal desorption spectroscopy. The microstructure and fracture surface of the specimens were characterized using X-ray diffraction, optical and scanning electron microscopy. The ductility loss after hydrogen charging was greater in the steel with higher nitrogen content. The fracture behavior is discussed in terms of austenite phase stability and the localization of slip in the presence of nitrogen and hydrogen. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: CR-MN STEELS; ENVIRONMENT EMBRITTLEMENT; MECHANICAL-PROPERTIES; NITROGEN; DEFORMATION; FRACTURE; STRESS; LOCALIZATION; PLASTICITY; STABILITY